Optimasi Kinerja Thermoelectric Generator (TEG) melalui Analisis Distribusi Kalor dan luaran Listrik dengan Variasi Sirip Penukar Panas - Atmoko, Nugroho Tri; Jamaldi, Agus; Ulikaryani, Ulikaryani; Pisti Cikarge, Ghia (Rekayasa, 2025)
The utilization of waste heat from conventional gas stoves as electrical energy represents an effort to improve household energy efficiency. Thermoelectric generator (TEG) technology enables the direct conversion of thermal energy into electrical energy without moving components. This study aims to investigate the performance of TEGs in harnessing waste heat from gas stoves through the application of various heat-sink fin configurations to enhance thermal absorption. Three types of fins—long fins, short fins, and random fins—were employed as heat exchangers and mounted on a modified stove enclosure. Four TEG modules were connected in series and tested to measure operating temperatures and the resulting electrical output. The findings indicate that fin configuration significantly influences heat distribution and TEG performance. The random fin model demonstrated the highest heat absorption capability, reaching 94.112 J/s, thereby increasing the temperature gradient across the TEG modules. Consequently, the random fin model also produced the highest electrical output, generating 3.369 Watts, outperforming the other fin designs. These results highlight the critical role of fin geometry in optimizing heat transfer within TEG systems. In conclusion, the random fin configuration is the most effective heat exchanger design for TEG applications on gas stoves, as it enhances heat absorption efficiency and delivers greater electrical power output. This finding offers important potential for further development of self-sustaining energy systems in household appliances.